PEMBIASAAN PERILAKU HIDUP BERSIH DAN SEHAT (PHBS) SISWA SMA NEGERI 13 PEKANBARU PADA MASA PANDEMI COVID-19 - Napitupulu, Novriyanti; Zainur, Zainur; Syahriadi, Syahriadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problem in this research is how SMA Negeri 13 Pekanbaru students conducted Habituation of Clean and Healthy Life Behavior during the pandemic covid-19. The purpose in this research was to find out the habituation of clean and healthy life behaviors of SMA Negeri 13 Pekanbaru students during the pandemic covid-19. The population in this study is all students of SMA Negeri 13 Pekanbaru which is as many as 477 people. The Sampling technique is a simple random sampling technique so that a sample of 119 people was obtained. The instrument used in this research is to use a questionnaire. The data obtained is analyzed using the percentage test technique (%). Based on an analysis of data from 119 people, 82 students (68.91%) who are in very good criteria, 36 students (30.25%) students who are in good criteria, and 1 student (0.84%) who are in sufficient criteria. This result means the Habituation of Clean and Healthy Life Behaviors of SMA Negeri 13 Pekanbaru Students During the Pandemic Covid-19 can be said to be "Very Good" with a percentage of 68.91%.Key Words: Clean and Healthy Life Behaviors, Pandemic Covid-19